In-Law Conflict Resolution from Christian and Muslim Religious Perspectives in Oriade, Nigeria - Isaac, Ubong Iniobong (Analisa: Journal of Social Science and Religion, 2025)
In-law conflict is a significant but often overlooked cause of marital problems in Nigeria, frequently leading to emotional distress and family breakdowns. Few studies have focused specifically on these disputes or compared how different religious groups manage them. This study addresses that gap by examining in-law conflicts among Christian and Muslim families in Oriade Local Government Area, a region known for its religious diversity. Based on family systems and conflict theory, this research used a qualitative design. Forty participants, 20 Christians and 20 Muslims, were interviewed across seven towns. Thematic analysis revealed shared causes of conflict, including cultural expectations, gender roles, and financial pressures. Cultural expectations, lack of educational exposure, and extended family interference were cited by over 65% of respondents. Domestic role expectations were more prominent among Muslim respondents (75%) than Christians (25%). Amid the conflict, religious leaders were central to conflict resolution in both faiths, with 77.5% of participants highlighting the importance of pastors and imams. However, polygamy was a unique challenge in Muslim households, while Christian families faced more generational tensions. Christian women often coped through silence and prayer, while Muslim women more openly demanded fairness. The study therefore recommends faith-based counselling, religious conflict resolution panels, safe spaces for women, and child-focused family education.